2010
DOI: 10.1111/j.1365-2672.2009.04548.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival and gene expression of enterotoxigenicEscherichia coliduring long-term incubation in sea water and freshwater

Abstract: Aims:  In this study, the main objective was to verify the hypothesis of induction of ‘viable but non‐culturable’ (VBNC) forms of enterotoxigenic Escherichia coli (ETEC) during incubation in water. Methods and Results:  Six clinically isolated ETEC strains were studied. Viable counts showed culturable ETEC bacteria for up to 3 months in freshwater but only two out of six strains were culturable in seawater at this time point. Although the bacterial cells remained intact, no production or secretion of heat‐labi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 26 publications
4
48
0
1
Order By: Relevance
“…A potential cause could be fresh human sewage input from sewage leakage and overflow; other likely sources include input from animal sources (32) and mobilization of E. coli surviving in the soil (33), sediments (34), and aquatic environment (35). These findings are in agreement with the previously reported observation of severalfold increase in FIB numbers in the surface water bodies after storm events (7)(8)(9).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A potential cause could be fresh human sewage input from sewage leakage and overflow; other likely sources include input from animal sources (32) and mobilization of E. coli surviving in the soil (33), sediments (34), and aquatic environment (35). These findings are in agreement with the previously reported observation of severalfold increase in FIB numbers in the surface water bodies after storm events (7)(8)(9).…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, the frequency of occurrence of EAEC pathotypes declined noticeably from 23 to 12% between the dry and wet periods. The observed decline in EAEC pathotypes and more uniform distribution of E. coli pathotypes after rainfall could possibly be due to mobilization of E. coli from point sources, such as wastewater treatment plant discharge, and nonpoint sources, such as animal sources (17,18,49,50) and E. coli surviving in the soil (33), sediments (34), and aquatic environment (35). This could also be a possible explanation of the observed increase (5 to 20%) in the frequency of occurrence of isolates which could be placed under more than one pathotype.…”
Section: Discussionmentioning
confidence: 99%
“…in wastewater seems to be longer at temperatures around 15°C (T99: 3.01 to 5.65) compared to 25°C (T99: 2.18) ( Table 3). In studies by Liang et al (2012) and Lothigius et al (2010), bovine, human, and pathogenic strains of E. coli spp. all persisted longer than generic E.coli spp in the experiments conducted.…”
Section: Bacteria and Bacterial Indicatorsmentioning
confidence: 99%
“…is frequently used as an indicator of human excreta and may not be an appropriate surrogate for looking at the survival of specific strains of E.coli, particularly those that may be human pathogens. Lothigius et al (2010) report that Enterotoxigenic E. coli (ETEC) had a T99 of 69.5 days at 21°C under natural sunlight conditions. In a similar study at 25°C, E. coli spp.…”
Section: Bacteria and Bacterial Indicatorsmentioning
confidence: 99%
“…The persistence and ability of ETEC to survive in these environments are mostly unknown. One study showed that ETEC was able to survive for up to 3 months in freshwater (713) and was able to form biofilms in drinking water sources (714). The infectious dose, compared to that of other E. coli pathotypes, is relatively high and is thought to be between 10 6 and 10 8 organisms (715).…”
Section: Epidemiologymentioning
confidence: 99%